1974
DOI: 10.2466/pms.1974.39.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Hyperempiria, a New “Altered State of Consciousness” Induced by Suggestion

Abstract: If the perception of one's own awareness is a subjective phenomenon, then trance-induction procedures may be devised which avoid the negative stereotypes and implicit authoritarian connotations which are inherent in the concept of hypnosis, while simultaneously facilitating responsiveness to suggestion. Previous attempts to accomplish this by modifications of the traditional hypnotic paradigm are discussed, and a new paradigm and induction procedure are presented.If hypnotizability is essentially role-taking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…If a dentist were merely to suggest to a patient that he would not experience any pain during a tooth extraction, for instance, with no induction administered beforehand, it is not likely that such a suggestion would be effective by itself, regardless of how responsive to suggestion the patient happened to be. But if the dentist were first to suggest that the patient was "entering a trance," and then he suggested that the patient would feel no pain, the latter suggestion could be actualized much more easily because it would then be much more credible (Gibbons, 1974).…”
Section: Director Of Special Projects Cushing Hospital Framingham Mamentioning
confidence: 99%
See 4 more Smart Citations
“…If a dentist were merely to suggest to a patient that he would not experience any pain during a tooth extraction, for instance, with no induction administered beforehand, it is not likely that such a suggestion would be effective by itself, regardless of how responsive to suggestion the patient happened to be. But if the dentist were first to suggest that the patient was "entering a trance," and then he suggested that the patient would feel no pain, the latter suggestion could be actualized much more easily because it would then be much more credible (Gibbons, 1974).…”
Section: Director Of Special Projects Cushing Hospital Framingham Mamentioning
confidence: 99%
“…Rather than concluding that these techniques are all variations of "hypnosis," it is more accurate to describe them as changes in perceived awareness which are brought about by means of suggestion, and which differ from hypnosis in the same way that they differ from each other: in the specific phenomenological content of the changes in perceived awareness which are either directly suggested or implied by the procedure which is utilized to bring about such changes, and, hence, in the "feel" of the resulting subjective experience of trance, and in the effect of that experience upon the subsequent thought and behavior of the subject who undergoes it (Gibbons, 1974). A highly responsive hypnotic subjectmay feel as if he has been unconscious, for example, and report that he remembers nothing of the events which transpired while he was supposedly under the influence of the "trance" (unless he has been previously told that he is not supposed to feel that way in hypnosis, or it has been specifically suggested to him that he will remember everything), whereas a student undergoing an advanced form of yogic training may feel as if he is merging with infinite reality!…”
Section: Director Of Special Projects Cushing Hospital Framingham Mamentioning
confidence: 99%
See 3 more Smart Citations